The Views of the Court of Arbitration for Sport and the Austrian Football Association on legal liability for the conduct of supporters - Vasilyev, Ilya; Margarita Izmalkova, Margarita; Khalatova, Raisa (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The clubs legal responsibility for the behavior of supporters is used by UEFA to in-fluence the content of sports competitions, ideally abstracted from demonstrating by spectators any non-football ideas. Nevertheless, the regulation of the national associa-tions-members of UEFA also assumes the responsibility of the clubs and, sometimes, the supporters themselves for the unacceptable behavior of the latter. The experience of regulation this issue by the Austrian Football Association demonstrates mentioned approach. Therefore, it is interesting to make a comparison: how much the regulated responsibility of supporters affects to the regulation by the association a strict liability of clubs for the behavior of fans. Using the practice of CAS, we may see a presumptive approach on the basis of an assessment of the situation by “a reasonable and objective observer” for the objective resolution of a dispute.